(untitled) (Al-Academy, 2025)
The twentieth century has produced most of the concepts in constructive criticism of scientific, philosophical and artistic experiences that came under the name of post-modernism, and the term (participation in the theatrical presentation) is one of the modern terms that came from the experiences of directors who rebelled against the realistic trend in art, including (Brecht, Artaud and many others), and through the research, the researcher concluded that participation, although it is a modern term, has deep roots in theatrical experiences throughout the historical ages since the time of the Greeks until now, and that post-modern directors tried to reach through making approaches with some historical experiences and theatrical philosophy for their directing style for the participatory theatrical presentation, and as a result, the researcher took in the theoretical framework the first topic (the space of the participatory presentation of the theater throughout the ages) and the second topic (the directorial works of the participation of the most prominent theatrical directors), and in the third procedural chapter he took the work of a multinational group (Belgian - Turkish ) With a presentation entitled (Gilgamesh) in which the director employed the participatory method and communicative interaction in terms of the spatial environment and the role of the recipient in the theatrical performance, and after that I reached the most prominent results and conclusions that had a positive effect in the participatory work of the theatrical performance .